Impact of Soil Heat Flux Attenuation on Surface Energy Balance Closure (2012)
In surface energy balance (SEB) measurements, ground heat flux (G) is either reconstructed from soil temperatures using analytical method or from the combination of calorimetric method with soil heat flux measured at 0.05 cm depth or more. Soil heat flux signal attenuation is known to increase with depth. This work intends to investigate the impact of this attenuation, which arises from the placement depths of soil temperature and heat flux plates sensors on SEB closure. Ground heat flux was reconstructed from soil heat flux and temperature measurements at two separate depths of 0.05 and 0.10 cm using calorimetric and analytical methods. The two data sets of G were combined with other SEB components to quantify the impact of placement depth of the soil sensors on SEB closure as a change in residual of SEB measurements (ΔRes). For the calorimetric method, the lowest value of ΔRes in the morning hours was -10W/m2 and the peak value during the daytime was +43W/m2. The values of ΔRes fluctuate between ±20 W/m2 in the morning hours and ±42W/m2 during the daytime for the analytical method but with a greater tendency towards positive ΔRes. Thus, SEB closure decreased with the increasing placement depth of the soil sensors, especially during the daytime. The implication of all these results is an irrecoverable signal loss in the soil heat flux as the placement depth of the sensors increases especially during the daytime.